[Co2(CO)6(Alkynyl)] Complexes of Dibenzosuberyl and Dibenzosuberenyl Carbocations: Dibenzotropylium or Dibenzoheptafulvene?. Issue 3 (6th January 2016) - Harris, Michelle; Brusey, Sarah A.; Moore, Angela; Ortin, Yannick; Müller‐Bunz, Helge; Manca, Gabriele; Mealli, Carlo; McGlinchey, Michael J.
Abstract: The reaction of dibenzo[ a, d ]cycloheptan‐5‐one (dibenzosuberone) and dibenzo[ a, d ]cyclohept‐10‐en‐5‐one (dibenzosuberenone) with aryl‐ or trimethylsilylacetylides led to the formation of the corresponding alkynyldibenzosuberols and alkynyldibenzosuberenols. Treatment with dicobalt octacarbonyl and then with bis(diphenylphosphino)methane (dppm) furnished the corresponding [Co2 (CO)4 (dppm)(alkynol)] clusters25 and29 . Upon protonation with HBF4 at 203 K to generate the relevant cobalt‐stabilised cations, the dibenzosuberyl system30 exhibited fluxionality such that the cation migrated between cobalt centres. Variable‐temperature 31 P NMR spectroscopy revealed a barrier of approximately 12.5 kcal mol −1 . In contrast, in the supposedly aromatic [Co2 (CO)4 (dppm)(dibenzosuberenyl)] + cation (31 ), which would be expected to have less need of cobalt stabilisation, the barrier was too high to be measured experimentally, but is certainly in excess of 16 kcal mol −1 . These data were rationalised by DFT calculations on the structures and energies of the relevant ground states and transition states, which suggested that the nonplanar alkynyldibenzosuberenyl moiety in31 is better regarded as a neutral dibenzoheptafulvene coordinated to a cationic alkynyl–dicobalt cluster. The question of the bonding of both aromatic and antiaromatic cations to alkyne–dicobalt clusters is considered, and it is proposed that their stabilities, when complexed, parallel the inversion of (4 n +2) π and 4 n π systems seen under photochemical conditions. Abstract : Turning things on their head : The observed high barrier to migration of the organic ligand between cobalt vertices in complex clusters suggests that the alkynyldibenzo[ a, d ]cycloheptenylium cation is better viewed as a dibenzoheptafulvene when coordinated to a cationic [Co2 (CO)6 ] fragment. DFT calculations reveal that coordination of the alkyne to a [Co2 (CO)6 ] unit inverts the aromatic (4 n +2) and antiaromatic (4 n ) character of cyclic substituents.